Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions



This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We have to prove that sum of n terms and the n+1 th term is equal to the sum according to the formula given.  This is the proof by Induction.

S_n=4\frac{1}{2*3}+8\frac{2}{3*4}+16\frac{3}{4*5}+..\ n\ terms.\\\\T_n=\frac{2^{n+1}*\ n}{(n+1)(n+2)}\\\\S_n=\frac{2^{n+2}}{n+2}-2\\\\Let\ n=1,\ \ \ 4\frac{1}{2*3}=\frac{2}{3}\\\\By\ formula\ S_1=\frac{2^3}{3}-2=\frac{2}{3,\ \ \ Formula\ holds.}\\\\Let\ S_n=\frac{2^{n+2}}{n+2}-2\ \ be\ true\ \ for\ n \ge 1\\\\S_{n+1}=\frac{2^{n+3}}{n+3}-2

S_{n+1}-S_n\\\\=\frac{2^{n+3}}{n+3}-\frac{2^{n+2}}{n+2}\\\\=\frac{(n+2)2^{n+3}-(n+3)2^{n+2}}{(n+3)(n+2)}\\\\=\frac{2^{n+2}*\ [2(n+2)-(n+3)]}{(n+3)(n+2)}\\\\=\frac{2^{n+2}*\ [n+1]}{(n+3)(n+2)}\\\\=T_{n+1}\\\\OR,\ \ S_{n+1}=S_n+T_n

Hence proved by Induction, as if the formula is good for  n, then it is good for n+1 also.

1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts